Record of Ragnarok. Vol. 3 - Umemura, Shin'ya; Fukui, Takumi (Viz signature., 2022)
"Once every millennium, the gods assemble to decide if humanity is worthy of its continued existence or if it should be destroyed! When the verdict is destruction, the final battle between the gods and mortal heroes will decide the survival or extinction of the human race--a battle known as Ragnarok! With humanity already down by one loss, the second round of the Ragnarok tournament is an unbelievable contest between Zeus, the father of all the Greek gods, and Adam, the very first human being! Up against the mighty Zeus, Adam may not look like much, but he has a few tricks hidden behind his fig leaf! Can he possibly take down the boss of Mount Olympus? As the second round comes to its dramatic end, the roaring crowd is already looking forward to the next matchup--Poseidon, the god of the seas, versus one of the greatest Japanese swordsmen ever, Sasaki Kojiro!"--Back cover.